Dual-functional recyclable luminescent sensors based on 2D lanthanide-based metal-organic frameworks for highly sensitive detection of Fe3+ and 2, 4-dinitrophenol. (November 2017) - Sun, Zan; Li, Yungai; Ma, Yue; Li, Licun
Abstract: A series of lanthanide-based metal-organic frameworks (Ln-MOFs), namely [Ln(L 2− )(HL – )(H2 O)2 ]n (Ln = Eu1, Gd2, Tb3 and Dy4, H2 L = 5-(imidazol-1-yl)isophthalic acid) have been successfully assembled under solvothermal conditions. Compounds1 –4 exhibit a 2D corrugated layer structure with 4 4 .6 2 - sql topology based on [Ln2 (CO2 )6 (H2 O)4 ] units containing uncoordinated carboxylate groups, which further forms a 3D supramolecular structure through hydrogen bond interactions. Compounds1 and3 display excellent applications as luminescent sensors for sensing 2, 4-dinitrophenol (2, 4-DNP) in ethanol system and Fe 3+ in aqueous solution with high sensitivity and selectivity based on luminescence quenching effects. Interestingly, 1 and3 display excellent recyclable behaviors and can be recycled at least 5 times for sensing 2, 4-DNP and Fe 3+ . These two compounds are the first reported dual-functional Ln-MOFs sensors for detecting 2, 4-DNP and Fe 3+ . Therefore, these two materials may be an excellent dual-functional recyclable luminescent sensor for 2, 4-dinitrophenol and Fe 3+ . Graphical abstract: Two novel lanthanide-based metal-organic frameworks (Ln = Eu and Tb) exhibit dual-functional luminescent sensors for the highly sensitive detection of Fe 3+ and 2, 4-dinitrophenol and display excellent recyclable behaviors. Highlights: Four isostructural 2D Ln-MOFs are obtained and exhibit an interesting 2D corrugated layer structure with sql topology. Eu and Tb compounds are the first reported dual-functional luminescent sensors which can sense 2, 4-dinitrophenol and Fe 3+ . Eu and Tb materials are excellent recyclable luminescent sensors for the detection of 2, 4-dinitrophenol and Fe 3+ .